INFLUENCE OF STRESS TRANSFER IN PROBABILITY ESTIMATES OF M≥6.5 EARTHQUAKES IN GREECE AND SURROUNDING AREAS - Paradisopoulou, P. M.; Papadimitriou, E. E.; Karakostas, V. G.; Lasocki, S.; Mirek, J.; Kilias, A. (Bulletin of the Geological Society of Greece, 2010)
The coseismic stress changes due to strong earthquakes (M>6.5) that occurred in Greece and its adjacent areas since the beginning of the 20th century (instrumental era) are calculated and the future seismic hazard expressed in terms of the probabilities of occurrence of M≥6.5 events is assessed. Calculations of the change in Coulomb failure stress reveal that 61 out of 67 ruptures were brought closer to failure by the preceding shocks. A new insight on the evaluation of future seismic hazards, in the study area, is given by translating the calculated coseismic stress changes into earthquake probability. We incorporated the effect of stress change into the time–depended probability estimates using an earthquake nucleation constitutive relation, which includes both permanent and transient effects of stress changes. Taking into account the current stress changes onto each major fault, the probability calculations were performed and given for the whole study area during the next 30 years